ZAKAT MANAGEMENT IN THE COVID-19 PANDEMIC ERA - Norvadewi, Norvadewi; Zaroni, Akhmad Nur; Rahmah, Fitria (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The study aims is to show how the zakat management in the covid-19 pandemic era. Amil zakat institutions need to make innovation in term of zakat management, both collection and distribution of zakat itself, one of them is related to the digitization of zakat management. This research analysed with a qualitative approach. The results showed that East Kalimantan LAZ DPU had innovated in terms of zakat management by utilizing digital technology both in the collection and distribution of ZIS funds. In the distribution of ZIS funds, it was directed at handling the impact of covid-19 for Mustahik to help Mustahik economic difficulties through regular programs in the field of humanity, da'wah, health, economy, and education. In addition, some special programs were also added, namely helping medical personnel by providing personal protective equipment, the best frontline nutrition program, providing basic food supply for the dhuafa, and empowering students and teachers during this pandemic. This research show that LAZ do an action in humanity specially in pandemic era